Risk Factors for Appendiceal Cancer After Appendectomy. Issue 6 (June 2021) - Stopenski, Stephen J.; Grigorian, Areg; Carmichael, Joseph; Mills, Steven; Brady, Matthew; Dolich, Matthew; Kuza, Catherine M.; Nguyen, Ninh T.; Nahmias, Jeffry
Background: Appendiceal cancer (AC) is a rare malignancy usually diagnosed incidentally after appendectomy. Risk factors for AC are poorly understood. We sought to provide a descriptive analysis for patients with AC discovered after appendectomy for acute appendicitis (AA). Methods: The 2016-2017 American College of Surgeons-National Surgical Quality Improvement Program Procedure-Targeted Appendectomy database was queried for adult patients who underwent appendectomy for image-suspected AA. Patients with pathology consistent with AA were compared to patients found to have AC. A multivariable logistic regression model was used for analysis. Results: From 21 058 patients, 203 (1.0%) were found to have AC on pathology. Compared to patients with AA, patients with AC were older (median, 48 vs. 40 years old, P < .001). The AA group had a similar rate of perforated appendix compared to the AC group (16.3% vs. 13.4% P = .32). After adjusting for covariates, associated risk factors for AC were: age ≥65 years old (odds ratio (OR) 2.25, 1.5-3.38, P < .001), absence of leukocytosis (OR 1.58, 1.16-2.17, P = .004), and operative time ≥1 hour (OR 1.57, 1.14-2.16, P = .006). Gender, race, and history of smoking were not independent associated risk factors for AC. Conclusion: The incidence of AC after appendectomy for suspected AA is approximately 1% in a large national analysis. These factors may be used to help identify patients at higher risk for AC after appendectomy.